Active Immobilized Antibiotics Based on Metal Hydroxides - Kennedy, John F. (1976)
The water-insoluble hydroxides of zirconium (IV), titanium (IV), titanium (III), iron (II), vanadium (III), and tin (II) have been used to prepare insoluble derivatives of a cyclic peptide antibiotic by a facile chelation process. Testing of the antibacterial activities of the products against two gram-positive and two gram-negative bacteria showed that in the majority of cases the water-insoluble antibiotics remained active against those bacteria susceptible to the parent antibiotic. The power of the assay system has been extended by the novel use of colored organisms to aid determinations where the growth of normal organisms could not be distinguished from the appearance of the supporting material. Insoluble derivatives of neomycin, polymyxin B, streptomycin, ampicillin, penicillin G, and chloramphenicol were prepared by chelation with zirconium hydroxide, and these derivatives similarly reflected the antibacterial activities of the parent compounds. Several of the metal hydroxides themselves possess antibacterial activity due to complex formation with the bacteria. However, the use of selected metal hydroxides can afford a simple, inexpensive, and inert matrix for antibiotic immobilization, resulting in an antibacterial product that may possess slow-release properties. The mechanisms by which the metal hydroxide-antibiotic association-dissociation may occur are discussed.